Pembuatan Kebun Binatang Virtual Untuk Pembelajaran Mengenai Binatang Liar - David Liemanto Gunawan; Liliana Liliana; Gregorius Satiabudhi (Jurnal Infra, 2016)
Along with increasingly learning methods evolving towards interactive learning, the technologies that supports it are also developed, from the use of computer applications, to the use of mobile devices. One of the technologies that are developed today is the technology of virtual reality. Currently the virtual reality technology can be used easily and with equipment that is easy to find around us. The system is made covering the process of making a virtual zoo for the game world, virtual animals that will fill the zoo, and a player that can be controlled by the user. Game world is a world that will be explored by the user and in this case is a zoo, and inside the zoo there are some virtual wild animals that have a state machines design to regulate the behavior and habits of each animal. This application is made using Google Cardboard Software Development Kit and Unity.Therefore, this thesis conducted by making an application to utilize virtual reality as an interactive and an attractive learning media, to study living wild animals for kids, with not only the theory but also with live demonstrations of the animal world. This application will run on android devices and using Google Cardboard as a medium for virtual reality.